2011
DOI: 10.1111/j.1600-051x.2010.01683.x
|View full text |Cite
|
Sign up to set email alerts
|

Open or submerged healing of implants with platform switching: a randomized, controlled clinical trial

Abstract: Platform-switched implants showed very limited peri-implant bone-level alterations. The healing-mode neither affected the total amount nor the temporal patterns of ΔIBL. Thus, the results for the tested implants with a non-rigid implant-abutment connection were similar to results reported previously for implants with a rigid implant-abutment connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 42 publications
9
45
0
3
Order By: Relevance
“…Other investigators have also showed similar results when comparing submerged and transmucosal implant placement protocols, but have reported different magnitudes of crestal bone‐level changes (Åstrand et al., ; Cecchinato et al., ; Cordaro, Torsello, & Roccuzzo, ; Enkling et al., ; Hermann, Buser, Schenk, & Cochran, ; Jung et al., ; Lambrecht, Filippi, Künzel, & Schiel, ; Sanz et al., ) suggesting that other factors, apart from the healing phase, may influence the stability of crestal bone levels. One of these factors could be related to the apico‐coronal position of the implant in relation to the bone crest (Schwarz, Hegewald, & Becker, ).…”
Section: Discussionmentioning
confidence: 80%
“…Other investigators have also showed similar results when comparing submerged and transmucosal implant placement protocols, but have reported different magnitudes of crestal bone‐level changes (Åstrand et al., ; Cecchinato et al., ; Cordaro, Torsello, & Roccuzzo, ; Enkling et al., ; Hermann, Buser, Schenk, & Cochran, ; Jung et al., ; Lambrecht, Filippi, Künzel, & Schiel, ; Sanz et al., ) suggesting that other factors, apart from the healing phase, may influence the stability of crestal bone levels. One of these factors could be related to the apico‐coronal position of the implant in relation to the bone crest (Schwarz, Hegewald, & Becker, ).…”
Section: Discussionmentioning
confidence: 80%
“…Ten of the 11 included studies were prospective RCTs (Becktor et al., ; Cecchinato et al., ; Cordaro et al., ; Eliasson et al., ; Engquist et al., ; Enkling et al., ; Gulati et al., ; Heijdenrijk et al., ; Nemli et al., ; Tallarico et al., ), while 1 was a prospective non‐RCT (Torkzaban et al., ). Six Studies had a parallel design (Becktor et al., ; Cordaro et al., ; Engquist et al., ; Heijdenrijk et al., ; Tallarico et al., ; Torkzaban et al., ), two had a mixed design (Cecchinato et al., ; Gulati et al., ) and the remaining three had a split‐mouth design (Eliasson et al., ; Enkling et al., ; Nemli et al., ). The follow‐up time, after implant placement ranged between 6 months and 5 years.…”
Section: Resultsmentioning
confidence: 99%
“…76 It also decreases the chances of errors. [40][41][42]52,[80][81][82][83][84][85][86][87][88][89][90] The line in the middle is called "the line of no effect," which has the value of 0. 77 However, RCT comes with its own limitations; notably cost, time, difficulty in studying rare events.…”
Section: Discussionmentioning
confidence: 99%
“…1 Radiographic reviews after the initial 5-year period revealed that when matching diameter implants and restorative components were used, the crestal bone contacting the implant normally remodeled to approximately 1.5 to 2 mm apically to the first thread. [47][48][49][50][51][52] Hence, this systematic review was done to examine the difference in the marginal bone-level changes when the implants were restored with platform-switched prostheses and to compare the efficiency of platform switching in reducing the marginal bone loss around the implants with platform-matched prostheses. The results were attributed to increase in surface area for soft tissue attachment and inward positioning of IAJ-associated inflammatory cell infiltrate away from the bone (biological advantage).…”
mentioning
confidence: 99%